The state and the country house in Nottinghamshire, 1937-1967 - Kempson, Matthew (2006)
This thesis considers the state preservation and use of Nottinghamshire country houses during the mid-twentieth century, from the initiation of mass requisition in 1937 until 1967 when concerns for architectural preservation moved away from the country house. This thesis reviews literature on the landed estate in the twentieth century and the emergence of preservationist claims on the country house. Three substantive sections follow. The first discusses the declining representation of landowners within local governance in Nottinghamshire and the constitution of the County Council, and considers how estate space was incorporated within broadened concerns for the preservation of the historic environment and additionally provided the focus for the implementation of a variety of modern state and non-state functions. The second section considers how changing policy and aesthetic judgements impacted upon the preservation of country houses. Through discussion of Rufford Abbey, Winkburn Hall and Ossington Hall I consider the complexities of preservationist claims and how these conflicted with the responsibilities of the state and the demands of private landowners. The third section considers how estate space became valued by local authorities in the implementation of a variety of new modern educational uses, including the teacher training college at Eaton Hall and a school campus development at Bramcote Hills. The thesis concludes by considering the status of the country house in Nottinghamshire since 1967, and contemporary demands on the spaces considered historically in this study.